2019
DOI: 10.1371/journal.pone.0227113
|View full text |Cite
|
Sign up to set email alerts
|

Indicators to distinguish symptom accentuators from symptom producers in individuals with a diagnosed adjustment disorder: A pilot study on inconsistency subtypes using SIMS and MMPI-2-RF

Abstract: In the context of legal damage evaluations, evaluees may exaggerate or simulate symptoms in an attempt to obtain greater economic compensation. To date, practitioners and researchers have focused on detecting malingering behavior as an exclusively unitary construct. However, we argue that there are two types of inconsistent behavior that speak to possible malingering—accentuating (i.e., exaggerating symptoms that are actually experienced) and simulating (i.e., fabricating symptoms entirely)—each with its own u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…Recently, researchers in different scientific fields, including the clinical and social sciences, have emphasized the utility of focusing on prediction, rather than explanation, during data analysis [ 69 , 70 , 71 , 72 ]. This increased attention to predictive models may be largely attributed to the significant spread of machine learning (ML)—a branch of artificial intelligence that trains algorithms on data samples (i.e., training sets) in order to make predictions on completely new data (i.e., test sets) without being explicitly programmed to do so [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, researchers in different scientific fields, including the clinical and social sciences, have emphasized the utility of focusing on prediction, rather than explanation, during data analysis [ 69 , 70 , 71 , 72 ]. This increased attention to predictive models may be largely attributed to the significant spread of machine learning (ML)—a branch of artificial intelligence that trains algorithms on data samples (i.e., training sets) in order to make predictions on completely new data (i.e., test sets) without being explicitly programmed to do so [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…ML algorithms automatically learn information from a set of data and make predictions on unseen data without being explicitly programmed to do so. ML techniques have been shown to be particularly useful in predicting human behavior, including high-risk behavior [ 48 , 49 , 50 , 51 ]. Indeed, one of the main advantages of ML is that it enables inferences to be made at the individual level, whereas traditional statistical methods focus primarily on the group level [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we extended the results reported by Mazza et al (2019c) (Bond, & Fox, 2015) treat selected items as local estimators of individual features. In classic psychometrics, linear correlation is usually the base for estimating item relevance in group discrimination tasks.…”
Section: Introductionmentioning
confidence: 61%
“…Malingering is the dishonest and intentional production or exaggeration of physical or psychological symptoms in order to obtain external gain (Tracy & Rix, 2017). Although malingering is coded in both the ICD-11 (World Health Organization, 2019) and the DSM-5 (American Psychiatric Association, 2013), it is not a binary "present" or "absent" phenomenon: it may exist in specific domains (e.g., psychological, cognitive, and medical domains), it is often comorbid with formal disorders (Mazza et al, 2019c;Rogers & Bender, 2018), and it can be classified into several types (Akca et al, 2020;Lipman, 1962;Resnick, 1997). Due to the considerable variation produced by these nuances, it is difficult to measure the prevalence of malingering in clinical and forensic populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation